Follicular lymphoma: updates for pathologists - Mahsa Khanlari; Jennifer R. Chapman (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Follicular lymphoma (FL) is the most common indolent B-cell lymphoma and originates from germinal center B-cells (centrocytes and centroblasts) of the lymphoid follicle. Tumorigenesis is believed to initiate early in precursor B-cells in the bone marrow (BM) that acquire the t(14;18)(q32;q21). These cells later migrate to lymph nodes to continue their maturation through the germinal center reaction, at which time they acquire additional genetic and epigeneticabnormalities that promote lymphomagenesis. FLs are heterogeneous in terms of their clinicopathologic features. Most FLs are indolent and clinically characterized by peripheral lymphadenopathy with involvement of the spleen, BM, and peripheral blood in a substantial subset of patients, sometimes accompanied by constitutional symptoms and laboratory abnormalities. Diagnosis is established by the histopathologic identification of a B-cell proliferation usually distributed in an at least partially follicular pattern, typically, but not always, in a lymph node biopsy. The B-cell proliferation is biologically of germinal center cell origin, thus shows an expression of germinal center-associated antigens as detected by immunophenotyping. Although many cases of FLs are typical and histopathologic features are straightforward, the biologic and histopathologic variability of FL is wide, and an accurate diagnosis of FL over this disease spectrum requires knowledge of morphologic variants that can mimic other lymphomas, and rarely non-hematologic malignancies, clinically unique variants, and pitfalls in the interpretation of ancillary studies. The overall survival for most patients is prolonged, but relapses are frequent. The treatment landscape in FL now includes the application of immunotherapy and targeted therapy in addition to chemotherapy.